The first cases of collagenous sprue successfully treated with thioguanine - Chris J J Mulder; Gerd Bouma; Tom van Gils; Tine van de Donk; Foke van Delft; E Andra Neefjes-Borst (BMJ Open Gastroenterology)
Objective Collagenous sprue (CS) is a rare form of small bowel enteropathy characterised by a thickened basement membrane and is, in most of the literature, reported as part of coeliac disease. Multiple treatment strategies are suggested in CS, but there is no standardised therapy. The aim of this series is to describe 4 cases of CS and to propose thioguanine (6-TG) treatment.Design We reviewed 4 cases of CS. Data were obtained from our prospective database of patients referred to our coeliac centre. Evaluation of small bowel biopsies was performed by an expert pathologist.Results None of the patients had ever had coeliac-specific antibodies, and all were negative for HLA-DQ2 and HLA-DQ8 phenotype. Three patients were treated with a combination of 6-TG and budesonide, and 1 patient received 6-TG only. All patients improved remarkably. Normalisation of the thickened basement membrane was found in 2 patients and complete histological improvement including full recovery of villi was found in 1 patient. In the third patient, the thickened basement membrane was only very focally recognised. The thickened membrane persisted in the last patient, probably because of the short time of follow-up.Conclusions CS should be separated from coeliac disease. Based on the lack of typical HLA phenotyping and the absence of coeliac-specific antibodies, there seems to be no relation with coeliac disease in these 4 cases. A promising treatment option might be 6-TG with or without budesonide. Research in a larger cohort is needed to standardise treatment for CS.